Unraveling isolated polycystic pancreatic disease: A clinical rarity and its review in literature - Gupta, Namit; Jhajharia, Ashok; Nitar, Vidhyadhar; Gupta, Anirudh; Pokharna, Rupesh; Ashdhir, Prachis (Indian Journal of Case Reports, 2026)
Pancreatic cysts are common, with pseudocysts being the most frequent. Polycystic pancreatic disease usually coexists with cysts in other solid organs, but isolated involvement of the pancreas is rare. This report presents a case of a 40-year-old female who presented with vague abdominal discomfort and pain with no history of pancreatitis or trauma. Radiological imaging showed multiple variable-sized thin-walled pancreatic cysts with no cystic lesions in the liver, spleen, kidneys, or brain. The patient was diagnosed with isolated polycystic disease of the pancreas and is on conservative management with regular follow-up. In summary, idiopathic isolated macro-polycystic disease of the pancreas is a rare condition that is usually asymptomatic with a benign outcome and is primarily diagnosed through imaging techniques, with magnetic resonance imaging being the most accurate. Further data and experience are needed to develop standardized treatment protocols in case of significant symptoms.